1982
DOI: 10.1029/jb087ib12p10265
|View full text |Cite
|
Sign up to set email alerts
|

Martian north polar cap 1979–1980

Abstract: A regression curve for the north polar cap of Mars is extracted from the photographs obtained at Kwasan Observatory and at Hida Observatory during the 1979–1980 apparition. The north polar cap was first observed at Ls = 26°, and the latitude of the edge of the cap was about 66°N. The retreat of the cap stopped until Mars reached Ls = 57° when the cap started to shrink. The edge reached a latitude around 80°N at Ls = 85° and then became almost stationary. The roughly constant dimension of the north polar cap be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
4
10
0
Order By: Relevance
“…The rates of seasonal polar cap recession observed by MOC James et al, 2000 are consistent with those observed previously from Earth-based [Fischbacher et al, 1969;Capen and Capen, 1970;Dollfus, 1973;Baum and Martin, 1973;Iwasaki et al, 1979Iwasaki et al, , 1982Iwasaki et al, , 1984Iwasaki et al, , 1999James et al, 1990] and spacecraft [Soderblom et al, 1973;Briggs, 1974;Christensen and Zurek, 1984;Cantor et al, 1998;James, 1979James, , 1982James and Lumme, 1982;James et al, 1979James et al, , 1987James et al, , 1996James et al, , 2000Kieffer et al, 2000] studies. However, the interior of the polar caps displayed substantial variations in albedo patterns from year to year.…”
Section: Seasonal Polar Capssupporting
confidence: 80%
“…The rates of seasonal polar cap recession observed by MOC James et al, 2000 are consistent with those observed previously from Earth-based [Fischbacher et al, 1969;Capen and Capen, 1970;Dollfus, 1973;Baum and Martin, 1973;Iwasaki et al, 1979Iwasaki et al, , 1982Iwasaki et al, , 1984Iwasaki et al, , 1999James et al, 1990] and spacecraft [Soderblom et al, 1973;Briggs, 1974;Christensen and Zurek, 1984;Cantor et al, 1998;James, 1979James, , 1982James and Lumme, 1982;James et al, 1979James et al, , 1987James et al, , 1996James et al, , 2000Kieffer et al, 2000] studies. However, the interior of the polar caps displayed substantial variations in albedo patterns from year to year.…”
Section: Seasonal Polar Capssupporting
confidence: 80%
“…This is the seasonal period when the plateau or standstill in the cap recession has been frequently reported previously (Iwasaki et al 1979(Iwasaki et al , 1982James 1979). There is no evidence for this effect in the average cap recession curve, Fig.…”
Section: Recessionmentioning
confidence: 74%
“…Antoniadi (1930), and Fischbacher et al (1969) summarized many of the early, prespacecraft, observations. More recent ground-based observers have included Dollfus (1973), Capen and Capen (1970), James et al (1987), and Iwasaki et al (1982Iwasaki et al ( , 1984Iwasaki et al ( , 1987Iwasaki et al ( , 1999. Mariner 9 (Soderblom et al 1973) and Viking (James 1979(James , 1982) also made north polar observations.…”
Section: Introductionmentioning
confidence: 91%
“…Confer Table IV. Dollfixs, 1973Dollfixs, ), 72" (1948Fischbacker et al, 1969Fischbacker et al, ), 73" (1963Capen, 1970), 72.5" (1963;Fischbacker et al, 1969Fischbacker et al, ), 73" (1963Parker et al, 1983Parker et al, ), 70" (1965Capen, 1970), 71" (1965;Fischbacker et al, 1969Fischbacker et al, ), 71" (1965Parker et al, 19X3), 65" (1967;Capen, 1970), 65" (1967;Parker et al, 1983Parker et al, ), 56" (1969Parker et al, 1983Parker et al, ), 73" (1978Iwasaki et al, 1979Iwasaki et al, ), 71" (1980Iwasaki et al, 1982), 71" (1980James, 1982James, ), 72" (1980McKim, ),-75"(1980Jamesetal., 1987bJamesetal., ),71"(1980Parkeretal., 1983Parkeretal., ),72" (1982Parker et al, 1983Parker et al, ), 70" (1982Iwasaki et al, 1984Iwasaki et al, ), 71" (1984Beish, 1996), 72" (1993;Troiani et al, 1996Troiani et al, ), 74" (1995Minami et al, 1995), and74" (1995;Parker and Beish, 1996).…”
Section: Discussion and Comparison With Earlier Workmentioning
confidence: 99%